Violence Against Woman In Thomas Hardy’s Work Tess Of The D’Urbervilles - Diyan Nofita Amelia; Mac Aditiawarman (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This research examines the forms of violence against women in Thomas Hardy’s Tess of the d’Urbervilles through the perspective of radical feminism as proposed by Rosemarie Tong (2009). The focus of the research is directed toward the depiction of Tess’s experiences as the main character who encounters physical, sexual, emotional, and verbal violence, while also exploring how the patriarchal social system influences the course of her life and destiny. The purpose of this research is to analyze how patriarchal power, as reflected through male characters and social institutions such as family, religion, and marriage, shapes Tess’s position as a woman who becomes a victim in a society biased against women, as well as to identify the various forms of violence experienced by Tess Durbeyfield in Hardy’s Tess of the d’Urbervilles. The approach applied is descriptive qualitative with the method of content analysis, in which the data are taken from narrative quotations, dialogues, and character interactions that portray practices of gender-based injustice. The findings reveal that Tess’s suffering is not merely the result of individual actions but is rooted in gender inequality institutionalized through cultural traditions, rigid social norms, and male dominance. Although Tess attempts to assert self-awareness, resilience, and courage to resist, her struggle often ends in defeat due to the strong grip of patriarchal values. In conclusion, Tess of the d’Urbervilles not only presents the tragic story of a woman’s life but also serves as a sharp social critique of gender-based power imbalances in the Victorian era, while remaining relevant in addressing discussions on gender equality and violence against women today.